1985
DOI: 10.1007/bf02066350
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic microfilaments in endothelial cells of flow loaded canine carotid arteries

Abstract: To observe cytoplasmic microfilaments in the endothelial cells of flow-loaded arteries, an arteriovenous shunt was constructed between the common carotid artery and the external jugular vein in 26 dogs. After measuring the flow rates of the arteries, the endothelial layer was examined ultrastructurally with a transmission electron microscope at three different times: 1 week (acute experiments), 2-4 weeks (subacute experiments), and 4-7 months (chronic experiments). Six-to seven-nanometer microfilaments were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…35 An increase in shear stress in canine common carotid artery following the creation of an arteriovenous shunt with the external jugular vein causes an increase in EC stress fibers. 26 These results indicate that the in vitro finding of orientation of stress fibers parallel to directional shear stress also occurs in vivo.…”
Section: Effects Of Shear Stress On Cytoskeleton Organization In Vivomentioning
confidence: 61%
See 1 more Smart Citation
“…35 An increase in shear stress in canine common carotid artery following the creation of an arteriovenous shunt with the external jugular vein causes an increase in EC stress fibers. 26 These results indicate that the in vitro finding of orientation of stress fibers parallel to directional shear stress also occurs in vivo.…”
Section: Effects Of Shear Stress On Cytoskeleton Organization In Vivomentioning
confidence: 61%
“…It has been suggested that the prominent stress fibers with clear orientation at regions exposed to high levels of directional flows may help the ECs to withstand hemodynamic stress and maintain vascular integrity. 26,39 Partial obstruction of arteries causes ECs in regions immediately downstream of the narrowing, where shear stress is low and unsteady, to become polygonal in shape with a loss of stress fiber orientation, in contrast to the EC elongation and stress fiber alignment with flow in regions of normal or high shear stress. 35 An increase in shear stress in canine common carotid artery following the creation of an arteriovenous shunt with the external jugular vein causes an increase in EC stress fibers.…”
Section: Effects Of Shear Stress On Cytoskeleton Organization In Vivomentioning
confidence: 99%
“…10 This morphological change is accompanied by cytoskeletal reorganization, with actin filaments becoming rearranged into bundles of stress fibers and aligned in the direction of the shear stress. [11][12][13] Vascular Tone When blood flow increases in vessels, they acutely dilate, and the dilation is mainly mediated by nitric oxide (NO) released by ECs. 14 A stimulatory effect of shear stress on NO production has been demonstrated in cultured ECs (Figure 1B), [15][16][17] and shear stress has been found to increase NO production via activation of endothelial NO synthase (eNOS) and upregulation of its gene expression.…”
Section: Morphologymentioning
confidence: 99%
“…In six of the shunted and in the two nonoperated animals, controlled pressure perfusion-fixatjon was carried out as described previously 20 by using 3% glutaraldehyde in phosphate buffer (pH 7.4). The height of an inflow reservoir and the outflow resistance were adjusted to maintain a constant perfusion pressure of 100 mm Hg.…”
Section: Tissue Preparationmentioning
confidence: 99%